Smart Nanostructured Materials based on Self‐Assembly of Block Copolymers. (12th June 2019) - Kim, Jang Hwan; Jin, Hyeong Min; Yang, Geon Gug; Han, Kyu Hyo; Yun, Taeyeong; Shin, Jin Yong; Jeong, Seong‐Jun; Kim, Sang Ouk
Abstract: Nanoscale fabrication of smart materials relying on the molecular self‐assembly of block copolymers (BCPs) has been recognized as a valuable platform for various next‐generation functional structures. In this Progress Report, the recent advances in the BCP self‐assembly process, which has paved the way for viable applications of emerging nanotechnologies, are highlighted. Effective light‐induced self‐assembly based on photothermal annealing of high‐χ BCPs and conformal 3D surface nanopatterning exploiting chemically modified graphene flexible substrates are reviewed as the typical instances of advanced BCP‐based nanofabrication methodologies. Additionally, relevant potential application fields are suggested, namely, graphene nanoribbon field effect transistors, highly tunable refractive index metasurfaces for visible light, high‐sensitivity surface‐enhanced Raman spectroscopy, 2D transition metal dichalcogenide nanopatterning, sequential infiltration synthesis, and organic photovoltaics. Finally, the future research direction as well as innovative applications of these smart nanostructured materials is proposed. Abstract : Nanofabrication relying on block copolymer (BCP) self‐assembly for smart nanostructured materials has attracted increasing attention as a smart nanofabrication strategy for next‐generation functional structures. This paper presents an overview of the recent advances in the BCP self‐assembly process and future outlook of the research direction for smart nanostructured materials.